University implementing its community service role through curriculum development in a regional college - Keerberg, Anne; Kiisla, Aet; Mäeltsemees, Sulev (Estonian Discussions on Economic Policy, 2014)
The three roles of a higher education institution are teaching, research and community service. The objective of the article is to analyse how a university regional college can implement the task of community service via its curriculum development. The theoretical base lies on the positions of internationally recognised scientists of education policy as well as OECD definitions and clarifications that are compared to the cases of the regional colleges (in Narva and Kuressaare) of two universities (respectively University of Tartu and Tallinn University of Technology). The set task enables to study as a whole such components as the content and design of curricula, teaching and assessment methods, extracurricular activities, topics and supervision of students’ research works, cooperation with partners. A comprehensive approach is a precondition of a well-functioning curriculum, with community service being the unifying aspect. The results of current study are applicable in case of the analysed curricula and colleges, they partly applicable in case of any other similar curricula and units. Prerequisites of the colleges' network evolvement, holistic impact and compliance with the region-specific needs is a significant topic the additional study of which hasalready begun.